Calcium-based phosphate hole sealing treatment method based on biomedical magnesium alloy micro-arc oxidation coating

By performing microarc oxidation treatment on the surface of biomedical magnesium alloy and adopting calcium-based phosphate pore sealing treatment, the problem of rapid degradation of magnesium alloy is solved, significantly improving the density and biocompatibility of the coating, and extending the service life of the implant.

CN119530926AInactive Publication Date: 2025-02-28NORTHEASTERN UNIV CHINA
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411737788.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The problem of rapid degradation of microarc oxidation coatings for biomedical magnesium alloys in the physiological environment has led to poor implantation effect, and the existing pore sealing treatment methods use rare earth elements or phosphate solutions, which have poor results.

Method used

The calcium-based phosphate pore sealing treatment method based on microarc oxidation treatment was adopted. After forming a microarc oxidation coating on the surface of the magnesium alloy, the pore sealing treatment was performed using a sealing solution containing soluble calcium salt, NH4H2PO4, NaNO3 and C10H14N2Na2O8·2H2O to fill the coating holes and increase the density through the phosphate deposition reaction.

Benefits of technology

The density and long-term degradation performance of the microarc oxidation coating of magnesium alloy are significantly improved, the effective protection time of the coating is extended, and the biocompatibility is improved by the introduction of calcium.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119530926A_ABST
    Figure CN119530926A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of material surface treatment, and particularly relates to a calcium-based phosphate hole sealing treatment method based on a biomedical magnesium alloy micro-arc oxidation coating. Carrying out micro-arc oxidation treatment on the magnesium alloy to obtain a micro-arc oxidation coating; and then hole sealing treatment is conducted in a hole sealing solution composed of calcium-based phosphate, the magnesium alloy surface micro-arc oxidation-calcium-based phosphate hole sealing composite coating is obtained, and the hole sealing solution is a mixed aqueous solution of soluble calcium salt, NH4H2PO4, NaNO3, C10H14N2Na2O8. 2H2O and H3PO4. After magnesium alloy is subjected to micro-arc oxidation treatment, a micro-arc oxidation coating formed on the surface has the defects of cracks, pores and the like, and the corrosion resistance of the coating is not facilitated. In order to further eliminate the influence of the defects in the coating, a novel calcium-based phosphate hole sealing treatment technology is adopted, so that the corrosion resistance of the coating can be remarkably enhanced, and the biocompatibility of the coating can be improved by introducing a calcium element.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of material surface treatment, and in particular to a calcium-based phosphate pore sealing treatment method based on a biomedical magnesium alloy micro-arc oxidation coating. Background Art

[0002] As an emerging degradable implant material, biomedical magnesium alloy has mechanical properties that match human bones, excellent biocompatibility and biodegradability. However, its rapid degradation in a physiological environment has become a major challenge in clinical applications. This rapid degradation makes it unable to provide stable support for tissue repair, thus affecting the implant effect. In order to solve this problem, surface treatment of magnesium alloys is particularly important. Surface treatment aims to improve the corrosion resistance, wear resistance and biocompatibility of magnesium alloys to extend their service life and ensure their safety and effectiveness in the body. Among many surface treatment technologies, micro-arc oxidation is favored due to its unique advantages.

[0003] Micro-arc oxidation technology uses the high temperature and high pressure generated by arc discharge to directly generate a layer of oxide ceramic coating that is firmly bonded to the substrate on the surface of the magnesium alloy. This coating can not only effectively resist corrosive media, but also has high hardness and wear resistance, protecting the stability of implants in the body. In addition, the micro-arc oxidation process is simple, efficient, and has little environmental pollution, which is in line with the concept of green and sustainable development. However, micro-arc oxidation coatings often have a porous structure, which makes the coating easily corroded in specific environments such as humid and corrosive media, and the long-term corrosion resistance of the coating is insufficient, thus failing to meet the degradation performance requirements of biomedical magnesium alloys.

[0004] Sealing the micro-arc oxidation coating is an effective method to improve the long-term corrosion resistance of the coating. The sealing liquids used in the current sealing treatment methods are mostly rare earth-based solutions or rare earth oxide particles. However, the content of rare earth elements in the human body is very small (less than 1 mg), and the effects of different rare earth elements on the human body are not yet fully understood. In recent years, some phosphate solutions have also been used to seal the micro-arc oxidation coating of magnesium alloys, but the sealing liquids in these sealing treatment methods only rely on the established number of cations in the solution and the magnesium ions dissolved from the magnesium alloy matrix to achieve the deposition and sealing of the corresponding phosphate, and the deposition and sealing effects are not good. Summary of the invention

[0005] In view of the deficiencies of the above-mentioned prior art, the purpose of the present invention is to provide a calcium-phosphate sealing treatment method based on a biomedical magnesium alloy micro-arc oxidation coating. The present invention first uses a micro-arc oxidation treatment method to make the magnesium alloy obtain a coating with good corrosion resistance, and then performs a sealing treatment to allow the sealing solution to fill the pores of the coating. Through the phosphate deposition reaction, the deposited material fills the pores and cracks in the micro-arc oxidation coating and is deposited on the surface of the micro-arc oxidation coating, thereby increasing the density of the micro-arc oxidation coating and improving the long-term degradation performance of the coating. The calcium content in the solution is increased by a compounding agent in the sealing solution to improve the sealing effect. At the same time, since calcium has the advantages of promoting osteogenesis, etc., the use of calcium-based phosphate for sealing treatment can further improve the biocompatibility of the coating.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0007] A calcium-based silicate pore sealing treatment method based on a biomedical magnesium alloy micro-arc oxidation coating comprises the following steps:

[0008] After the magnesium alloy samples are cut, they are polished step by step, and then cleaned and dried.

[0009] The treated magnesium alloy sample is used as an anode and a graphite plate is used as a cathode. The sample is placed in an electrolyte for micro-arc oxidation treatment, and then rinsed and dried to obtain a micro-arc oxidation coating.

[0010] The micro-arc oxidation coating is sealed in a sealing solution to obtain a micro-arc oxidation-calcium-based phosphate sealing composite coating on the surface of the magnesium alloy.

[0011] The sealing solution is soluble calcium salt, NH4H2PO4, NaNO3 and C 10 H 14 A mixed aqueous solution of N2Na2O8·2H2O.

[0012] The present invention first uses a micro-arc oxidation treatment method to obtain a coating with good corrosion resistance on the magnesium alloy, and then performs a sealing treatment to fill the pores of the coating with a sealing solution. Through a phosphate deposition reaction, the deposited material fills the pores and cracks in the micro-arc oxidation coating and is deposited on the surface of the micro-arc oxidation coating, thereby increasing the density of the micro-arc oxidation coating and improving the long-term degradation performance of the coating. The Ca(NO3)2·4H2O compounding agent in the sealing solution is used to increase the calcium content in the solution, thereby improving the sealing effect. At the same time, since calcium has the advantages of promoting osteogenesis, etc., the biocompatibility of the coating can be further improved by using calcium-based phosphate for sealing treatment.

[0013] In a preferred embodiment of the present invention, the soluble calcium salt is Ca(NO3)2·4H2O or CaCl2, and the sealing solution contains Ca(NO3)2·4H2O, NH4H2PO4, NaNO3, C 10 H 14 The usage ratio of N2Na2O8·2H2O and water is 30g~40g:30g~40g:2g~4g:2g~5g:1L.

[0014] In a preferred embodiment of the present invention, the sealing treatment temperature is 60°C to 70°C.

[0015] In a preferred embodiment of the present invention, before the sealing treatment, 10% H3PO4 is used to adjust the pH value of the sealing solution to 3-4.

[0016] In a preferred embodiment of the present invention, the micro-arc oxidation treated coating is immersed in the sealing solution for 10 minutes to 30 minutes.

[0017] In a preferred embodiment of the present invention, the electrolyte is a mixed aqueous solution of Na2SiO3·9H2O, KF·2H2O, and NaOH.

[0018] In a preferred embodiment of the present invention, in the electrolyte, the usage ratio of Na2SiO3·9H2O, KF·2H2O, NaOH and water is 20g~25g:7g~8g:8g~10g:1L.

[0019] In a preferred embodiment of the present invention, the micro-arc oxidation process parameters are: voltage 0-450V, current density 3A / cm 2 ~5A / cm 2 , pulse frequency 100Hz~500Hz, duty cycle -30%~30%.

[0020] In a preferred embodiment of the present invention, the micro-arc oxidation treatment time is 30 min to 35 min.

[0021] In a preferred embodiment of the present invention, the magnesium alloy is a Mg-0.45Zn-0.45Ca alloy.

[0022] In a preferred embodiment of the present invention, the method of grinding the sample step by step after cutting is to grind it with 240#, 600#, 1000# and 2000# SiC sandpaper in sequence.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. The calcium-phosphate sealing method of the present invention first uses a micro-arc oxidation treatment method to prepare a micro-arc oxidation coating, and then performs a sealing treatment on the micro-arc oxidation coating to fill the coating pores with a sealing solution, and through a phosphate deposition reaction, the deposited material fills the pores and cracks in the micro-arc oxidation coating and is deposited on the surface of the micro-arc oxidation coating, thereby increasing the density of the micro-arc oxidation coating and improving the long-term degradation performance of the coating. The soluble calcium salt compound in the sealing solution is used to increase the calcium content in the solution to improve the sealing effect. At the same time, since calcium has the advantages of promoting osteogenesis, etc., the use of calcium-based phosphate for sealing treatment can further improve the biocompatibility of the coating.

[0025] 2. The present invention first performs micro-arc oxidation treatment to obtain a micro-arc oxidation coating with good corrosion resistance, and then adopts a new calcium-based phosphate sealing process to finally generate a wear-resistant and corrosion-resistant composite coating on the surface. After the magnesium alloy is treated with micro-arc oxidation, the micro-arc oxidation coating formed on its surface often has defects such as cracks and pores, which are not conducive to the long-term corrosion resistance of the coating. In order to further eliminate the influence of these defects in the coating, the new calcium-based phosphate sealing treatment technology is adopted, which can not only deposit phosphates in the coating defects to improve the density of the coating and significantly enhance the corrosion resistance of the coating, but also improve the biocompatibility of the coating by introducing calcium elements. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a macroscopic image of the magnesium alloy surface film prepared in Example 1 of the present invention.

[0027] Figure 2 Surface electron microscope scanning images of the magnesium alloy surface films prepared in Comparative Example 1(a) and Example 1(b) of the present invention.

[0028] Figure 3 The cross-sectional electron microscope images are of the magnesium alloy cross-sectional films prepared in Comparative Example 1(a) and Example 1(b) of the present invention.

[0029] Figure 4 This is the energy spectrum of the magnesium alloy surface film prepared in Example 1 of the present invention.

[0030] Figure 5 The potentiodynamic polarization curve of the magnesium alloy surface film prepared in Example 1 of the present invention.

[0031] Figure 6 Electrochemical impedance spectrum of the magnesium alloy surface film prepared in Example 1 of the present invention, (a) electrochemical impedance spectrum, (b) Bode diagram.

[0032] Figure 7 This is a comparison chart of the magnesium alloy surface film immersion experiment prepared in Comparative Example 1 (a) and Example 1 (b) of the present invention. DETAILED DESCRIPTION

[0033] The following is a detailed description of the technical solutions in the embodiments of the present invention in combination with the preferred embodiments and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] It should be noted that all professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.

[0035] The present invention aims at the problem that the sealing solution in the traditional magnesium alloy sealing treatment method only relies on the predetermined number of cations in the solution and the magnesium ions dissolved from the magnesium alloy matrix to achieve the deposition and sealing of the corresponding phosphate, but the deposition and sealing effects are not good. A magnesium alloy surface micro-arc oxidation-calcium-based phosphate sealing treatment method is proposed. A magnesium alloy sample is used as an anode and a graphite plate is used as a cathode. The magnesium alloy sample is placed in an electrolyte for micro-arc oxidation treatment to obtain a micro-arc oxidation coating; the micro-arc oxidation coating is placed in a solution containing soluble calcium salt, NH4H2PO4, NaNO3, C 10 H 14 The magnesium alloy surface is sealed by micro-arc oxidation-calcium-phosphate sealing treatment coating in a sealing solution of N2Na2O8·2H2O, wherein the sealing solution contains soluble calcium salt, NH4H2PO4, NaNO3, C 10 H 14 The dosage ratio of N2Na2O8·2H2O to water is 30-40g:30-40g:2-4g:2-5g:1L; the results show that the pores of the micro-arc oxidation film after sealing with calcium-based phosphate are significantly reduced, and the immersion experiment after 90 days of immersion in simulated body fluid proves that the corrosion resistance of the sample after phosphate sealing treatment is significantly better, indicating that the present invention uses micro-arc oxidation treatment to obtain a coating with good corrosion resistance on the surface of the magnesium alloy, retains the good corrosion resistance of the surface coating of the alloy after micro-arc oxidation treatment, and makes the sealing solution fill the pores of the coating while phosphate deposition occurs, thereby filling the holes in the coating. This method can improve the density of the micro-arc oxidation coating of the magnesium alloy, and greatly prolong the time for the coating to effectively protect the magnesium alloy substrate, solves the problem of holes on the surface of the coating formed after micro-arc oxidation, and greatly prolongs the service life.

[0036] Example 1

[0037] A surface micro-arc oxidation-calcium-based phosphate sealing treatment method for a Mg-0.45Zn-0.45Ca alloy comprises the following steps:

[0038] (1) The Mg-0.45Zn-0.45Ca alloy was cut into a semi-cylindrical shape with a height of 10 mm and a diameter of 10 mm, and polished with 240#, 400#, 600#, 1000# and 2000# SiC sandpaper in sequence, and then cleaned with ethanol and blown dry.

[0039] (2) preparing an electrolyte of 22.5 g / L Na2SiO3·9H2O, 7.5 g / L KF·2H2O and 9 g / L NaOH; then using the sample obtained in step (1) as an anode and the graphite plate as a cathode, the samples were placed in the electrolyte for micro-arc oxidation treatment in a constant current mode, wherein the voltage of the pulse power supply was 450 V and the current density was 3 A / cm 2 The pulse frequency is 500 Hz, the duty cycle is positive 30% and negative 30%, and the micro-arc oxidation is carried out for 30 minutes. After the oxidation, the sample is taken out, rinsed with deionized water and blown dry.

[0040] (3) First, prepare 35.4 g / L of Ca(NO3)2·4H2O, 35 g / L of NH4H2PO4, 2 g / L of NaNO3 and 2.23 g / L of C 10 H 14 A sealing solution of N2Na2O8·2H2O is prepared, and the pH value of the sealing solution is adjusted to 3 using 10% H3PO4. The sealing solution is then heated to 60°C, and the sample obtained in step (2) is placed therein for 10 minutes. The sample is then taken out, rinsed with deionized water, and blown dry to obtain a micro-arc oxidation coating treated with calcium-based phosphate sealing.

[0041] Example 2

[0042] A surface micro-arc oxidation-calcium-phosphate sealing method for a Mg-0.45Zn-0.45Ca alloy comprises the following steps:

[0043] (1) The Mg-0.45Zn-0.45Ca alloy was cut into a shape of 10 mm × 10 mm × 5 mm, and polished with 240#, 400#, 600#, 1000# and 2000# SiC sandpaper in sequence, and then cleaned with ethanol and blown dry.

[0044] (2) preparing an electrolyte of 22.5 g / L Na2SiO3·9H2O, 7.5 g / L KF·2H2O and 9 g / L NaOH; then using the sample obtained in step (1) as an anode and the graphite plate as a cathode, the samples were placed in the electrolyte for micro-arc oxidation treatment in a constant current mode, wherein the voltage of the pulse power supply was 450 V and the current density was 3 A / cm 2 The pulse frequency is 500 Hz, the duty cycle is positive 20% and negative 30%, and the micro-arc oxidation is carried out for 40 minutes. After the oxidation, the sample is taken out, rinsed with deionized water and blown dry.

[0045] (3) First, prepare 35.4 g / L of Ca(NO3)2·4H2O, 35 g / L of NH4H2PO4, 2 g / L of NaNO3 and 2.23 g / L of C 10 H 14 A sealing solution of N2Na2O8·2H2O is prepared, and the pH value of the sealing solution is adjusted to 3 using 10% H3PO4. The sealing solution is then heated to 65°C, and the sample obtained in step (2) is placed therein for 15 minutes. The sample is then taken out, rinsed with deionized water, and blown dry to obtain a micro-arc oxidation coating treated with calcium-based phosphate sealing.

[0046] Example 3

[0047] A surface micro-arc oxidation-calcium-phosphate sealing method for a Mg-0.45Zn-0.45Ca alloy comprises the following steps:

[0048] (1) The Mg-0.45Zn-0.45Ca alloy was cut into a shape of 15 mm × 15 mm × 5 mm, and polished with 240#, 400#, 600#, 1000# and 2000# SiC sandpaper in sequence, and then cleaned with ethanol and blown dry.

[0049] (2) First, an electrolyte solution of 23.5 g / L Na2SiO3·9H2O, 7.5 g / L KF·2H2O and 9.5 g / L NaOH was prepared; then, the sample obtained in S1 was used as the anode and the graphite plate was used as the cathode, and the sample was placed in the electrolyte solution for micro-arc oxidation treatment in a constant current mode, wherein the voltage of the pulse power supply was 450 V and the current density was 3 A / cm 2 The pulse frequency is 500 Hz, the duty cycle is positive 20% and negative 20%, and the micro-arc oxidation lasts for 35 minutes. After the oxidation, the sample is taken out, rinsed with deionized water and blown dry.

[0050] (3) First, prepare 35.4 g / L of Ca(NO3)2·4H2O, 35 g / L of NH4H2PO4, 2 g / L of NaNO3 and 2.23 g / L of C 10 H 14A sealing solution of N2Na2O8·2H2O is prepared, and the pH value of the sealing solution is adjusted to 3.5 using 10% H3PO4. The sealing solution is then heated to 70°C, and the sample obtained in step (2) is placed therein for 20 minutes. The sample is then taken out, rinsed with deionized water, and blown dry to obtain a micro-arc oxidation coating treated with calcium-based phosphate sealing.

[0051] Example 4

[0052] A surface micro-arc oxidation-calcium-phosphate sealing method for a Mg-0.45Zn-0.45Ca alloy comprises the following steps:

[0053] (1) The Mg-0.45Zn-0.45Ca alloy was cut into a shape of 20 mm × 20 mm × 10 mm, and polished with 240#, 400#, 600#, 1000# and 2000# SiC sandpaper in sequence, and then cleaned with ethanol and blown dry.

[0054] (2) Prepare an electrolyte containing 23.5 g / L Na2SiO3·9H2O, 7.5 g / L KF·2H2O and 9 g / L NaOH. Then, the sample obtained in step (1) is used as an anode and the graphite plate is used as a cathode. The sample is placed in the electrolyte for micro-arc oxidation treatment in a constant current mode. The voltage of the pulse power supply is 450 V and the current density is 3 A / cm 2 The pulse frequency is 500 Hz, the duty cycle is positive 30% and negative 20%, and the micro-arc oxidation is carried out for 40 minutes. After the oxidation, the sample is taken out, rinsed with deionized water and blown dry.

[0055] (3) First, prepare 35.4 g / L of Ca(NO3)2·4H2O, 35 g / L of NH4H2PO4, 2 g / L of NaNO3 and 2.23 g / L of C 10 H 14 A sealing solution of N2Na2O8·2H2O is prepared, and the pH value of the sealing solution is adjusted to 3.5 using 10% H3PO4. The sealing solution is then heated to 70°C, and the sample obtained in step (2) is placed therein for 25 minutes. The sample is then taken out, rinsed with deionized water, and blown dry to obtain a micro-arc oxidation coating treated with calcium-based phosphate sealing.

[0056] Example 5

[0057] A surface micro-arc oxidation-calcium-based phosphate sealing treatment method for a Mg-0.45Zn-0.45Ca alloy comprises the following steps:

[0058] (1) The Mg-0.45Zn-0.45Ca alloy was cut into a semi-cylindrical shape with a height of 10 mm and a diameter of 10 mm, and polished with 240#, 400#, 600#, 1000# and 2000# SiC sandpaper in sequence, and then cleaned with ethanol and blown dry.

[0059] (2) preparing an electrolyte of 20 g / L Na2SiO3·9H2O, 7 g / L KF·2H2O and 8 g / L NaOH; then using the sample obtained in step (1) as an anode and the graphite plate as a cathode, the samples were placed in the electrolyte for micro-arc oxidation treatment in a constant current mode, wherein the voltage of the pulse power supply was 450 V and the current density was 3 A / cm 2 The pulse frequency is 500 Hz, the duty cycle is positive 30% and negative 30%, and the micro-arc oxidation is carried out for 30 minutes. After the oxidation, the sample is taken out, rinsed with deionized water and blown dry.

[0060] (3) First, prepare 35.4 g / L of Ca(NO3)2·4H2O, 35 g / L of NH4H2PO4, 2 g / L of NaNO3 and 2.23 g / L of C 10 H 14 A sealing solution of N2Na2O8·2H2O is prepared, and the pH value of the sealing solution is adjusted to 4 using 10% H3PO4. The sealing solution is then heated to 60°C, and the sample obtained in step (2) is placed therein for 15 minutes. The sample is then taken out, rinsed with deionized water, and blown dry to obtain a micro-arc oxidation coating treated with calcium-based phosphate sealing.

[0061] Example 6

[0062] A surface micro-arc oxidation-calcium-based phosphate sealing treatment method for a Mg-0.45Zn-0.45Ca alloy comprises the following steps:

[0063] (1) The Mg-0.45Zn-0.45Ca alloy was cut into a semi-cylindrical shape with a height of 10 mm and a diameter of 10 mm, and polished with 240#, 400#, 600#, 1000# and 2000# SiC sandpaper in sequence, and then cleaned with ethanol and blown dry.

[0064] (2) preparing an electrolyte of 25 g / L Na2SiO3·9H2O, 8 g / L KF·2H2O and 10 g / L NaOH; then using the sample obtained in step (1) as an anode and the graphite plate as a cathode, the samples were placed in the electrolyte for micro-arc oxidation treatment in a constant current mode, wherein the voltage of the pulse power supply was 450 V and the current density was 3 A / cm 2 The pulse frequency is 500 Hz, the duty cycle is positive 30% and negative 30%, and the micro-arc oxidation is carried out for 30 minutes. After the oxidation, the sample is taken out, rinsed with deionized water and blown dry.

[0065] (3) First, prepare 40 g / L of Ca(NO3)2·4H2O, 40 g / L of NH4H2PO4, 4 g / L of NaNO3 and 5 g / L of C 10 H 14 A sealing solution of N2Na2O8·2H2O is prepared, and the pH value of the sealing solution is adjusted to 4 using 10% H3PO4. The sealing solution is then heated to 80°C, and the sample obtained in step (2) is placed therein for 10 minutes. The sample is then taken out, rinsed with deionized water, and blown dry to obtain a micro-arc oxidation coating treated with calcium-based phosphate sealing.

[0066] Comparative Example 1

[0067] A surface micro-arc oxidation-calcium-phosphate sealing method for a Mg-0.45Zn-0.45Ca alloy comprises the following steps:

[0068] (1) The Mg-0.45Zn-0.45Ca alloy was cut into a semi-cylindrical shape with a height of 10 mm and a diameter of 10 mm, and polished with 240#, 400#, 600#, 1000# and 2000# SiC sandpaper in sequence, and then cleaned with ethanol and blown dry.

[0069] (2) preparing an electrolyte of 22.5 g / L Na2SiO3·9H2O, 7.5 g / L KF·2H2O and 9 g / L NaOH; then using the sample obtained in step (1) as an anode and the graphite plate as a cathode, the samples were placed in the electrolyte for micro-arc oxidation treatment in a constant current mode, wherein the voltage of the pulse power supply was 450 V and the current density was 3 A / cm 2 The pulse frequency is 500 Hz, the duty cycle is positive 30% and negative 30%, and the micro-arc oxidation is carried out for 30 minutes. After the oxidation, the sample is taken out, rinsed with deionized water and blown dry.

[0070] The preparation methods of Examples 2-5 of the present invention are the same as those of Example 1, with the only difference being that, when experimental conditions permit, the amounts of certain raw materials and reaction conditions are changed, but this does not affect the performance of the obtained micro-arc oxidation coatings. Therefore, the micro-arc oxidation coatings obtained in Examples 2-5 have similar performance to that of Example 1, and can both improve the density of the micro-arc oxidation coatings on magnesium alloys and greatly prolong the time that the coatings effectively protect the magnesium alloy substrate.

[0071] Results Analysis

[0072] Figure 1 This is a macroscopic image of the surface film of the Mg-0.45Zn-0.45Ca alloy prepared in Example 1 of the present invention, as shown in Figure 1 As shown, it can be seen that the coating color of the surface film of the Mg-0.45Zn-0.45Ca alloy is white.

[0073] Figure 2 The surface electron microscope scanning images of the surface films of the Mg-0.45Zn-0.45Ca alloys prepared in Example 1 and Comparative Example 1 of the present invention; wherein (a) is Comparative Example 1, and (b) is Example 1. Figure 2 (b) shows that only micro-arc oxidation is performed Figure 2 (a) Compared with Example 1, the pores of the surface film of the sample treated by the micro-arc oxidation-calcium phosphate sealing method on the surface of the Mg-0.45Zn-0.45Ca alloy in Example 1 were significantly reduced. This is mainly because after the calcium-based phosphate sealing treatment, the calcium-based phosphate is deposited on the surface of the coating, thereby filling the holes in the coating and improving the density of the magnesium alloy micro-arc oxidation coating.

[0074] Figure 3 The cross-sectional electron microscope scanning images of the surface films of the Mg-0.45Zn-0.45Ca alloys prepared in Example 1 and Comparative Example 1 are shown in FIG. 1 , wherein (a) is Comparative Example 1 and (b) is Example 1. Figure 3 As shown in (b), the coating prepared in Example 1 is tightly bonded to the interface of the substrate, and the surface coating of the sample treated with micro-arc oxidation-calcium-phosphate sealing on the surface of the Mg-0.45Zn-0.45Ca alloy is about 15 to 20 μm.

[0075] Figure 4 The energy spectrum of the surface film of the Mg-0.45Zn-0.45Ca alloy prepared in Example 1 is as follows: Figure 4 As shown, Example 1 is subjected to micro-arc oxidation treatment and then to calcium-phosphate sealing treatment. The Mg-0.45Zn-0.45Ca alloy micro-arc oxidation coating mainly contains Mg, Si, and O, and the sealing material mainly contains Ca, P, and O.

[0076] Figure 5 The potentiodynamic polarization curve of the Mg-0.45Zn-0.45Ca alloy surface film prepared in Example 1 is shown in FIG. Figure 5 As shown in the figure, Example 1 was treated by micro-arc oxidation and then sealed with calcium-based phosphate. The electrochemical impedance corrosion current density of the alloy decreased significantly compared with that of the Mg-0.45Zn-0.45Ca alloy, from 2.8×10 -6 A / cm 2 Down to 1.0×10 -7 A / cm 2 , its corrosion resistance is significantly improved.

[0077] Figure 6The electrochemical impedance spectra of the Mg-0.45Zn-0.45Ca alloy sample prepared in Example 1 after micro-arc oxidation treatment and then calcium-based phosphate sealing treatment and the sample prepared in Comparative Example 1 without calcium-based phosphate sealing treatment are as follows: Figure 6 As shown in the figure, the electrochemical impedance of Example 1 after micro-arc oxidation treatment and then calcium-based phosphate sealing treatment is significantly improved compared with the Mg-0.45Zn-0.45Ca alloy treated with micro-arc oxidation alone, from 2.01×10 6 Ω increased to 5.05×10 6 Ω.

[0078] Figure 7 The Mg-0.45Zn-0.45Ca alloy sample prepared by the present invention after micro-arc oxidation treatment and then calcium-phosphate sealing treatment was compared with the sample without calcium-phosphate sealing treatment after immersion in simulated body fluid for 90 days, wherein (a) is comparative example 1, (b) is example 1, and Figure 7 As shown in the figure, the corrosion resistance of the samples treated with calcium-based phosphate sealing is significantly better.

[0079] In summary, the present invention first performs micro-arc oxidation treatment to obtain a coating with good corrosion resistance, and then adopts a new calcium-based phosphate sealing process to finally generate a wear-resistant and corrosion-resistant coating on the surface. After the magnesium alloy is treated with micro-arc oxidation, the micro-arc oxidation coating formed on its surface maintains excellent corrosion resistance. In order to further eliminate the problem of pores on this film, the phosphate sealing treatment technology is used, which not only successfully fills the micropores on the surface of the micro-arc oxidation coating, but also significantly enhances the corrosion resistance of the coating.

[0080] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0081] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A calcium-phosphate pore sealing method based on biomedical magnesium alloy micro-arc oxidation coating, characterized in that: The following steps are involved: A magnesium alloy sample was used as an anode and a graphite plate was used as a cathode, and the samples were placed in an electrolyte for micro-arc oxidation treatment to obtain a micro-arc oxidation coating. The micro-arc oxidation coating is subjected to a sealing treatment in a sealing solution to obtain a calcium-based phosphate sealing composite coating based on biomedical magnesium alloy micro-arc oxidation; The sealing solution is soluble calcium salt, NH4H2PO4, NaNO3 and C 10 H 14 The mixed aqueous solution of N2Na2O8·2H2O, the concentration of soluble calcium salt is 30g / L~40g / L, the concentration of NH4H2PO4 is 30g / L~40g / L, the concentration of NaNO3 is 2g / L~4g / L, C 10 H 14 The concentration of N2Na2O8·2H2O is 2g / L~5g / L.

2. The calcium-phosphate pore sealing treatment method based on biomedical magnesium alloy micro-arc oxidation coating according to claim 1, characterized in that: Soluble calcium salts are Ca(NO3)2·4H2O or CaCl2.

3. The calcium-phosphate pore sealing treatment method based on biomedical magnesium alloy micro-arc oxidation coating according to claim 1, characterized in that: The sealing treatment temperature is 60℃~70℃.

4. The calcium-phosphate pore sealing treatment method based on biomedical magnesium alloy micro-arc oxidation coating according to claim 1, characterized in that: Before the sealing treatment, 10% H3PO4 was used to adjust the pH value of the sealing solution to 3-4.

5. The calcium-phosphate pore sealing treatment method based on biomedical magnesium alloy micro-arc oxidation coating according to claim 1, characterized in that: The micro-arc oxidation treated coating is immersed in the sealing solution for 10 minutes to 30 minutes.

6. The calcium-based phosphate sealing treatment method based on biomedical magnesium alloy micro-arc oxidation coating according to claim 1, characterized in that: The electrolyte is a mixed aqueous solution of Na2SiO3·9H2O, KF·2H2O and NaOH.

7. The calcium-based phosphate sealing treatment method based on biomedical magnesium alloy micro-arc oxidation coating according to claim 6, characterized in that: In the electrolyte, the usage ratio of Na2SiO3·9H2O, KF·2H2O, NaOH and water is 20g~25g:7g~8g:8g~10g:1L.

8. The calcium-phosphate pore sealing treatment method based on biomedical magnesium alloy micro-arc oxidation coating according to claim 1, characterized in that: The micro-arc oxidation process parameters are: voltage 0-450V, current density 3A / cm 2 ~5A / cm 2 , pulse frequency 100Hz~500Hz, duty cycle -30%~30%.

9. The calcium-phosphate pore sealing treatment method based on biomedical magnesium alloy micro-arc oxidation coating according to claim 1, characterized in that: The micro-arc oxidation treatment time is 30min to 35min.

10. The calcium-based phosphate pore sealing treatment method based on biomedical magnesium alloy micro-arc oxidation coating according to claim 1, characterized in that: The magnesium alloy is Mg-0.45Zn-0.45Ca alloy.

Citation Information

Cited By

  • Preparation method and device of structure and function integrated bionic interbody fusion cage

    CN121081171A